Emotional responses to branded and unbranded foods. (June 2015) - Spinelli, S.; Masi, C.; Zoboli, G.P.; Prescott, J.; Monteleone, E.
Highlights: Sensory properties are powerful elicitors of emotions. Brand elicit positive emotions when communication is coherent with expectations. Complete assimilation is related to an improvement of the emotional performance (EP). When a disconfirmation is not followed by an assimilation, the EP get worse. Abstract: Investigating the emotions elicited by a product considering only its sensory characteristics or both its sensory characteristics and packaging/branding can give a deeper insight into product perception and can help companies in the design and optimisation of products that meet consumer expectations. The aim of this study was to (i) measure how liking changes across blind, package (expected) and informed conditions, and (ii) measure how emotions change across blind and informed conditions, in products representing the widest range of sensory variability and brand identity in the market category of hazelnut and cocoa spreads. In the first session participants ( n  = 120) tasted each product in a blind condition, expressed their liking and rated emotions using the EmoSemio questionnaire specifically developed for this product category (Spinelli, Masi, Dinnella, Zoboli, & Monteleone, 2014). Then consumers were asked to rate their expected liking for the products, presented in the original packaging by means of photos (pack/expected condition). After one week, consumers tasted each product presented with its own packaging (informed condition), expressed their liking and rated emotions. Emotions were very discriminating in both conditions: in the informed condition all the emotions significantly varied across samples, while in the blind condition 21 out of 23 (91.3%) varied. Results showed a correlation between liking (blind, expected and informed) and emotions. Complete assimilation of liking toward expectations was associated to an overall improvement of the emotional performance of the product: positive emotions increased in the case of complete assimilation towards the expectations, while negative emotions decreased. When there was a mismatch between expected liking evoked by packaging and blind liking (disconfirmation) but an assimilation effect was not found, some positive emotions significantly decreased in the informed condition compared to the blind one. This study suggests the importance of collecting emotion responses in both blind and informed conditions to detect changes in the emotional profile of products due to the brand/packaging providing information useful for product optimisation.